Strategi Komunikasi Pemasaran Dalam Meningkatkan Konsumen Pada PT. Altic Houseware - Clarita Apriyanti; Nur Rahmah Amini (Yayasan Rahmat Islamiyah, 2022)
The purpose of research to determine the communication strategy in improving customers on PT. Altic Houseware. This research uses a type of descriptive research with a qualitative approach. Descriptive research involves collecting data to test hypotheses or answer questions about the state subject of research. The most common type of descriptive research involves the evalution of attitude or opinion of individuals, organization, situation, or procedure. This study was conducted on PT. Altic Houseware Jl. HM. Joni no 53. Data collection techniques used in this study are interviews are data collection techniques that use oral questions to research subjects. The marketing communication strategy carried out by PT.Altic Houseware in proving customer is good enough. This, the author can know from the resylts of an interview with source, namely consumers where they think that the strategies carroed out through social media have been able to channel information abaout the product price so that it makes consumers interested in coming directly to PT. Altic Houseware.